Inequality of educational opportunities and the role of learning intensity: Evidence from a quasi-experiment in Germany - Sebastian Camarero Garcia (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Over the 2000s, many federal states in Germany shortened the duration of secondary school by one year while keeping the curriculum unchanged. Exploiting quasi-experimental variation due to the staggered introduction of this reform allows me to identify the causal effect of increased learning intensity on Inequality of Educational Opportunity (IEOp), the share in educational outcome variance explained by predetermined circumstances beyond a student's control. The reform-induced increase in learning intensity had no short-term effect on IEOp. In the medium term, however, IEOp increased as differences in parental resources gained importance through support opportunities like private tuition adapting to the intensified educational process. The effect is stronger for mathematics/science than for reading, implying the existence of subject-dependent curricular flexibilities. My findings point to the importance of accounting for distributional consequences when evaluating reforms aimed at increasing the efficiency of educational systems and to the role of learning intensity for explaining changes in educational opportunities influencing social mobility.
urn:nbn:de:bsz:180-madoc-456979
Keywords: D04; D63; H75; I21; I24; I28; J18; J24; J62; O52; 330; (In)Equality of Opportunity; Educational/Learning Intensity; shortening school duration; G-8 education reform; Education & Social Mobility; Germany